2019
DOI: 10.1111/ibi.12800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extra‐pair paternity and maternity on the provisioning strategies of the Azure‐winged Magpie Cyanopica cyanus

Abstract: Altricial birds show enormous intraspecific diversity in their provisioning strategies, in terms of both the provisioning rate and the amount of food delivered per feeding bout. Extra‐pair copulations (EPCs), which result in either extra‐pair paternity (EPP) or maternity (EPM), provide an opportunity to demonstrate why provisioning strategies vary among individuals. Because EPP‐cuckolded males and EPM‐cuckolded females must raise unrelated young, whereas EPM‐cuckolded males and EPP‐cuckolded females need not, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Choices related to male age may also differ depending on the social context. For example, some female song birds choose middle-aged males with territories as social mates, but may also engage in extra-unit copulations with younger males ( Griffith et al 2002 ; Gao et al 2019 ).…”
mentioning
confidence: 99%
“…Choices related to male age may also differ depending on the social context. For example, some female song birds choose middle-aged males with territories as social mates, but may also engage in extra-unit copulations with younger males ( Griffith et al 2002 ; Gao et al 2019 ).…”
mentioning
confidence: 99%
“…Extra-pair paternity (EPP) is suggested to be associated with the parental care in Remizidae (Ball et al 2017) and the amount of parental investment in animals in general (Kvarnemo 2018;Gao et al 2020;Schrader et al 2020). However, according to our microsatellite analyses, EPP is relatively low in Chinese penduline tits (around 6%,36 nests,198 nestlings,HW et al unpublished data), which is similar to Cape penduline tits Anthoscopus minutus (5.4%, Ball et al 2017) that obligate biparental care.…”
Section: Female Parental Care and Mating Opportunitiesmentioning
confidence: 50%
“…Empirical work in birds (e.g. western bluebirds Sialia Mexicana [13], black redstarts [9], scarlet rosefinches Carpodacus erythrinus [14] and azure-winged magpies Cyanopica cyanus [15]), fishes (e.g. the plainfin midshipman Porichthys notatus [16], and the cichlid Variabilichromis moori [7]) and the burying beetle (Nicrophorus vespilloides) [17], however, found that males do not seem to detect cuckoldry or react to it [for instance, in western bluebirds [13], males did not reduce paternal effort even when they observed their mate engaging in extra-pair copulations (EPCs)].…”
Section: Introductionmentioning
confidence: 99%